Physicochemical Properties and Antimicrobial Activity of Evaporated Extract of Cow Dung Against Some Pathogens - Waziri, M.; Suleiman, J. S. (Journal of Scientific Research, 2012)
The evaporated extract of cow dung is traditionally used in Northern Nigeria and Cameroun as food additive and in treatment of infectious diseases. In this study, the cow dung ash extract was prepared and tested for some elemental contents as well as the antimicrobial activity against Cyanobacteria (C.bacteria), Staphylococcus aureus (S.aureus), Bacillus subtilis (B.subtilis) and Escherichia coli (E.coli) using different analytical techniques. The extract was highly basic with pH of 11.7 and the elements vary in the following decreasing order of concentration; K>Na>Mg>Ca>Fe>Al>Zn. S. aureus was the most sensitive bacteria with minimum inhibitory concentration (MIC) value of 0.082 mg/mL while B. subtilis was the least sensitive with MIC value of 4.3 mg/mL. The result of this study indicate that the extract can supplement the dietary Na and K requirements for the users and supports the folkloric use of the extract in treatment of infections. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i1.11962 J. Sci. Res. 5 (1), 135-141 (2013)